IMPLEMENTASI ALGORITMA APRIORI UNTUK MENENTUKAN POLA PEMBELIAN PADA KOLEGA COFFEE - via nabila banda; Ade Eviyanti; Uce Indahyanti (Politeknik Bisnis Indonesia, 2023)
Kolega Coffee is one of the coffee shops that sells a variety of coffee variants and other menus. The sold menus will be recorded in the sales system for the sales report. The increasing number of visitors generates a lot of sales transaction data. And the data only serves as sales reports and archives. However, if the data is processed further, it will acquire new information for decision-making in business strategy. The research aims to find menus that are often purchased simultaneously through sales transaction data from January to June 2023 using a priori algorithm whose rule has the advantage of being able to know patterns of purchasing products at the same time. by defining frequent itemsets that are useful to form association rules. The results of this study resulted in five association rules from 1917 sales transaction data. For example, if someone buys onion rings, they're also likely to buy a mix platter with a 38.33% confidence rate. This study can give advice for business strategies to coffee colleagues for example for promotion of menu packages or other discounts.